THE INFLUENCE OF COSTUMER RELATIONSHIP MANAGEMENT TOWARD CUSTOMER LOYALTY IN PT. BANK NEGARA INDONESIA (PERSERO) TBK. MANADO - Pangkey, Monika; Saerang, David P.E. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2014)
New Economy Market is rapidly growing with internet, which is offering choice for customer. Internet technology makes it easier to discover what the customers want, understands the values that are important to individual customers, and implement cost-effective and results-driven CRM strategies. BNI as one of the major bank in Indonesia use the customer relationship management concept to maintain the existing customer to be a customer loyalty. The purpose of this research is to analyze how is the influence of CRM to the customer loyalty and to identify which factors of CRM such as promotion, lottery, event sponsorship and customer service consultant that have the most significant influence to the customer loyalty of BNI in Manado. The research method that used in this research associative with multiple linear regression analysis technique, as sample of the research 100 respondent taken from customers of BNI Manado. The finding revealed that only customer service consultant have significant effect to the customer loyalty of BNI Manado. They should pay attention on how to maintain this program, made the customer feels comfort by serving management, be friendly and providing helpful staff. Keywords: customer relationship management, customer loyalty